2017
DOI: 10.1017/s0266078417000293
|View full text |Cite
|
Sign up to set email alerts
|

Investigating perceptions of English as a lingua franca in Hong Kong: The case of university students

Abstract: English as a lingua franca (ELF) has received a great deal of attention in the field of applied linguistics in the last decade or so (Jenkins, 2007, 2014; Mauranen, 2012; Seidlhofer, 2011). As is currently conceptualized, ELF refers to the common language of choice among speakers from different lingua-cultural backgrounds (Jenkins, 2007; Seidlhofer, 2011). ELF does not imply a single, unified variety of English but primarily refers to language in use in contexts where multilingual speakers are involved (Cogo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
4
22
0
Order By: Relevance
“…On the other hand, another participant was somewhat ambivalent in his answers overall, stating 'learning' for his own English and 'sharing' for partner students' English, and 'because I use it in university' for why English is important, and somewhat agreed to want to sound like a native speaker. Thus, as their overall attitude, our participants manifested the pervasive tendency among ELF users that previous research witnesses -being ambivalent (Sung 2018;Jenkins, 2007;Takahashi, 2017;Rahatlou et al 2018;Jaramillo et al 2020;Lai, 2020).…”
Section: Overall Tendency: Being Ambivalent After Allmentioning
confidence: 69%
See 2 more Smart Citations
“…On the other hand, another participant was somewhat ambivalent in his answers overall, stating 'learning' for his own English and 'sharing' for partner students' English, and 'because I use it in university' for why English is important, and somewhat agreed to want to sound like a native speaker. Thus, as their overall attitude, our participants manifested the pervasive tendency among ELF users that previous research witnesses -being ambivalent (Sung 2018;Jenkins, 2007;Takahashi, 2017;Rahatlou et al 2018;Jaramillo et al 2020;Lai, 2020).…”
Section: Overall Tendency: Being Ambivalent After Allmentioning
confidence: 69%
“…Many citizens of the European Union (EU) countries can be typical ELF users, as they mainly use English with people from other European countries or other continents in various social milieus (Seidlhofer 2020) -from political summits to the Eurovision Song Contest. Substantial research in various geographical contexts has investigated attitudes of university students (often pre-service English teachers) and English teachers, who can be framed as 'ELF users' according to our criteria (e.g., Cogo 2010;Curran and Chern 2017;Dewey and Pineda 2020;Jenkins 2007;Sung 2018;Takahashi 2017;Rahatlou, Fazilatfar, and Allami 2018;Sung 2018;Jaramillo, Dávila, and Jarquín, 2020;Lai 2020). While some studies in this body of research found that pedagogical intervention foster positive attitudes towards English as ELF (e.g., Chacón-Beltrán 2021; Delgado-Marín 2018; Dewey and Pineda 2020), many report that ELF user attitudes are usually not straightforward but rather ambivalent, mixed, inconsistent, and often selfcontradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FLCAS questionnaire consisted of 33 questions validated using Pearson Correlation Coefficient from SPPS 22. The reliability of the internal consistency of the scale was measured by using Alpha Cronbach coefficient as guided the following table 1 (Sugiyono, 2011): Students' total score from the questionnaire was calculated to see the students' levels of foreign language anxiety: high, moderate, and low anxiety levels. In order to know the index of each level, the researchers used the formula below: Finally, the researcher calculated the score of the total frequency.…”
Section: Methodsmentioning
confidence: 99%
“…In this era of globalization, the need to master foreign languages is increasing. English as a lingua franca makes English become the language commonly used as a liaison between countries with different languages of instruction and speakers (Iriance, 2018;Liu, 2019;Mauranen, 2018;Sherman, 2018;Sung, 2017). Various countries in Southeast Asia have designated English as the number one foreign language taught and studied at various education system levels (Handayani, 2016;Kirkpatrick, 2018;Kirkpatrick & Liddicoat, 2017).…”
Section: Introductionmentioning
confidence: 99%